Mengkaji Implementasi Kurikulum 2013 Mata Pelajaran Pendidikan Agama Islam di SMAN 1 Dander dan SMAN 1 Bojonegoro - Samsu, Mokhamad (JOIES (Journal of Islamic Education Studies), 2016)
The result of this research shows that the implementation of 2013 Curriculum of Islamic Religious Education in SMAN 1 Dander and SMAN 1 Bojonegoro has been started since 2013. The principals’ efforts to succeed the 2013 Curriculum can be seen from their encouragement for teachers to join teacher associations, workshops or teacher trainings. The teachers also adjust teaching materials with the 2013 curriculum, make the students accustomed to perform worship, guide those who cannot read the Qur’an yet, and follow the principal’s recommendation. Supporting factors of implementing the 2013 Curriculum in these two schools consist of the availability of adequate facilities and competent teachers. However, there are some obstacles found in these two schools in implementing the 2013 curriculum, such as the lack of students’ discipline to attend either inside or outside classroom activities and the lack of some parents’ attention to their children